Ethnobotanical knowledge in Javanese Rituals as contextual resources for biology education - M. Mualimin; Rahmania Pamungkas; Nilahazra Khoirunnisa; Anggitya Nareswari; Kuntum Febriyantiningrum (University of Muhammadiyah Malang, 2025)
Indonesia’s rich plant biodiversity and cultural heritage are closely reflected in traditional life cycle ceremonies—such as birth, marriage, and death—which often involve specific plant species. Ethnobotany, the study of human-plant interactions, serves as a bridge between traditional knowledge and modern science. This descriptive qualitative study, based on a literature review, identifies various plant species used in Javanese rituals. Birth ceremonies involve 14 species, while marriage rituals utilize between 24 and 47 species, predominantly from the Zingiberaceae family. Death rituals incorporate at least 24 species, with variations across regions. These findings reveal that ethnobotanical practices are not only expressions of cultural identity but also possess educational significance. In the context of secondary biology education, this knowledge offers a valuable foundation for developing contextual and culturally relevant learning materials, particularly for teaching biodiversity, plant taxonomy, and ecology. Integrating local wisdom into science instruction can enhance student engagement, promote meaningful learning, and strengthen both plant and cultural literacy. This study underscores the potential of ethnobotany in supporting character-based and contextual learning aligned with current curriculum goals.